Meta‐Analysis of Gene Expression Patterns in Animal Models of Prenatal Alcohol Exposure Suggests Role for Protein Synthesis Inhibition and Chromatin Remodeling. (20th March 2016) - Rogic, Sanja; Wong, Albertina; Pavlidis, Paul
Abstract : Background: Prenatal alcohol exposure (PAE) can result in an array of morphological, behavioral, and neurobiological deficits that can range in their severity. Despite extensive research in the field and a significant progress made, especially in understanding the range of possible malformations and neurobehavioral abnormalities, the molecular mechanisms of alcohol responses in development are still not well understood. There have been multiple transcriptomic studies looking at the changes in gene expression after PAE in animal models; however, there is a limited apparent consensus among the reported findings. In an effort to address this issue, we performed a comprehensive re‐analysis and meta‐analysis of all suitable, publically available expression data sets. Methods: We assembled 10 microarray data sets of gene expression after PAE in mouse and rat models consisting of samples from a total of 63 ethanol (EtOH)‐exposed and 80 control animals. We re‐analyzed each data set for differential expression and then used the results to perform meta‐analyses considering all data sets together or grouping them by time or duration of exposure (pre‐ and postnatal, acute and chronic, respectively). We performed network and Gene Ontology enrichment analysis to further characterize the identified signatures. Results: For each subanalysis, we identified signatures of differential expressed genes that show support from multiple studies. Overall, the changes in gene expression were more extensive after acute EtOH treatment during prenatal development than in other models. Considering the analysis of all the data together, we identified a robust core signature of 104 genes down‐regulated after PAE, with no up‐regulated genes. Functional analysis reveals over representation of genes involved in protein synthesis, mRNA splicing, and chromatin organization. Conclusions: Our meta‐analysis shows that existing studies, despite superficial dissimilarity in findings, share features that allow us to identify a common core signature set of transcriptome changes in PAE. This is an important step to identifying the biological processes that underlie the etiology of fetal alcohol spectrum disorders. Abstract : We performed a meta‐analysis of 10 gene expression profiling studies of rodent models of prenatal alcohol exposure (PAE), with the goal of finding commonalities across the studies and determining biological processes that underlie the etiology of FASD. We identified genes consistently differentially expressed across studies, despite the reports of the original studies being largely discordant. Functional analysis suggests PAE acts as a net inhibitor of gene expression, especially effecting genes involved in protein synthesis, mRNA splicing, and chromatin organization.